2010
DOI: 10.1186/1742-4755-7-25
|View full text |Cite
|
Sign up to set email alerts
|

Generating demand and community support for sexual and reproductive health services for young people: A review of the Literature and Programs

Abstract: BackgroundThis review investigates the effectiveness of interventions aimed at generating demand for and use of sexual and reproductive health (SRH) services by young people; and interventions aimed at generating wider community support for their use.MethodsReports and publications were found in the peer-reviewed and grey literature through academic search engines; web searches; the bibliographies of known conference proceedings and papers; and consultation with experts. The studies were reviewed against a set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 20 publications
2
49
0
1
Order By: Relevance
“…Although the focus of this review is on health service delivery, certainly many other interventions, such as health education [3,74], are also needed to improve health among marginalized youth. Although many of the studies in this review included some health education component, only Townsend et al's analysis of a project in Monterrey, Mexico provided some insight into the relative importance of the components [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the focus of this review is on health service delivery, certainly many other interventions, such as health education [3,74], are also needed to improve health among marginalized youth. Although many of the studies in this review included some health education component, only Townsend et al's analysis of a project in Monterrey, Mexico provided some insight into the relative importance of the components [55].…”
Section: Discussionmentioning
confidence: 99%
“…These approaches aim to reach youth where they are-schools, workplaces, detention facilities, youth centers, on the street, etc. Assessments have been made of such community-based messaging approaches, identifying successes, failures, and gaps in knowledge regarding their effectiveness [3][4][5][6][7][8][9][10]. In addition to improving knowledge, attitudes, and behaviors, access to HIV and reproductive health services and commodities is also vital to reducing mortality and improving the health of youth-both in terms of their current and future adult health status.…”
mentioning
confidence: 99%
“…contraception use. It is clear that young people need both accurate information on SRH, as well as the ability to navigate the overwhelming amount of inaccurate information in order to make healthy and well-informed choices [24]. …”
Section: Methodsmentioning
confidence: 99%
“…The application of such approaches has shown to increase the quality of health service provision in a number of countries. Experience from a number of countries has shown that without concerted efforts to create community support for health service provision to adolescents and adolescent demand for their use, improving the quality of health provision alone will not lead to increased service utilization (10). Given this, the evaluation points to clear actions for the Tarunya Project.…”
Section: Discussionmentioning
confidence: 99%